Frailty as a Predictor of Mortality in Elderly Iranians Residing in Nursing Home Facilities - Mehdi Norouzi; Zahra Amiri; Masoumeh Sadeghi; Mohaddese Neshat Iranpour; Ali Taghipour; Tahereh Khosravi Asl; Ehsan Mosafarkhani (Iran University of Medical Sciences, 2024)
Background: Frailty is a common geriatric syndrome associated with adverse health outcomes in older adults. This study aimed to examine the association between frailty index and mortality in elderly residents of nursing homes in Iran. Methods: This historical cohort study used data extracted from the Sina Electronic Health Record System (SinaEHR®, Iran) and the national cause of death registry in Iran. The study population included 9199 adults aged ≥60 assessed for frailty in nursing homes across Iran from April 2021 to June 2022. They were followed up until August 2022. Frailty was defined as a score >3 on Fried's 5-item index. We used multivariable logistic regression to determine adjusted odds ratios (ORs) with 95% confidence intervals (CIs) for mortality-related factors. The chi-square test compared mortality across groups. Data were analyzed using Stata software, version 11 with P<0.05 as the significance level.  Results: Of 9199 subjects, 3566(38.7%) were frail, and 5643(61.3%) were non-frail. During follow-up, 3354(36.5%) deaths occurred. Frailty was associated with 2.49 times higher odds of mortality (95% CI, 2.27%, 2.74%; P<0.001) compared to the non-frail state after adjustment for covariates. Older age (P<0.001), female sex (P<0.001), and comorbidities (P<0.001) were also significant predictors of mortality. Conclusion: Frailty index strongly predicts mortality risk in Iranian elderly nursing home residents. Assessing and managing frailty may help reduce adverse outcomes in this vulnerable population.